Cinematic Shevchenkiana of the late Stalinist times on the pages of the Ukrainian newspaper "Svoboda" in the USA. - Grinchenko , Victor (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Purpose of the study. To review and analyse the article by the Ukrainian historian, publicist, and public figure Mykola Chubatyi “Ukraine and Shevchenko in the Soviet Film”, published in August 1952 in the Ukrainian newspaper “Svoboda”, which was published in the USA. The article discusses the new Soviet feature film “Taras Shevchenko” directed by Ihor Savchenko, which was shown in the USA at that time. Research methodology. The principles of historicism, objectivity, comprehensiveness, and integrity of the source study were applied. Descriptive, comparative-historical, and historico-critical methods were used. Scientific novelty. The materials presented in this publication can serve as an addition to the existing scientific research on the disclosure of individual components of the cinematic Shevchenkiana, in particular by representatives of the intellectual elite of the Western Ukrainian diaspora. Conclusions. It was concluded that M. Chubatyi aimed to form an idea among the readers of “Svoboda” about the falsification of Shevchenko in Soviet cinema, the distortion of historical truth, and to show the biased image of the poet presented in this film. He believes that the film was produced to serve the Kremlin’s ideology aimed at continuing and strengthening its rule over Ukraine. Despite the largely negative reviews of various episodes of this film, M. Chubatyi still finds a certain artistic value in some of its aspects. The judgments given in the analysed publication by M. Chubatyi are mainly confirmed in the works of other researchers from the Western Ukrainian diaspora and among contemporary authors in independent Ukraine.